2022
DOI: 10.3390/genes13010156
|View full text |Cite
|
Sign up to set email alerts
|

Drought, Low Nitrogen Stress, and Ultraviolet-B Radiation Effects on Growth, Development, and Physiology of Sweetpotato Cultivars during Early Season

Abstract: Drought, ultraviolet-B (UV-B), and nitrogen stress are significant constraints for sweetpotato productivity. Their impact on plant growth and development can be acute, resulting in low productivity. Identifying phenotypes that govern stress tolerance in sweetpotatoes is highly desirable to develop elite cultivars with better yield. Ten sweetpotato cultivars were grown under nonstress (100% replacement of evapotranspiration (ET)), drought-stress (50% replacement of ET), UV-B (10 kJ), and low-nitrogen (20% LN) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Furthermore, individual genotype stress response index of the shoot, root, and physiological parameters or cumulative temperature response index was used to identify potential low- and high-temperature tolerant carinata genotypes ( Figure 6 ), similar to other recent studies ( Bheemanahalli et al, 2021 ; Reddy et al, 2021 ; Ramamoorthy et al, 2022 ). Among the genotypes studied, genotype AX17009 recorded a superior root system (no change in roots between low and optimum temperatures) coupled with shoot and physiology responses than the sensitive genotype (AX17010) at the early vegetative stage.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…Furthermore, individual genotype stress response index of the shoot, root, and physiological parameters or cumulative temperature response index was used to identify potential low- and high-temperature tolerant carinata genotypes ( Figure 6 ), similar to other recent studies ( Bheemanahalli et al, 2021 ; Reddy et al, 2021 ; Ramamoorthy et al, 2022 ). Among the genotypes studied, genotype AX17009 recorded a superior root system (no change in roots between low and optimum temperatures) coupled with shoot and physiology responses than the sensitive genotype (AX17010) at the early vegetative stage.…”
Section: Resultsmentioning
confidence: 72%
“…Cumulative low-temperature response index (CLTRI) and cumulative high-temperature response index (CHTRI) values were calculated using the standardized vigor index ( Wijewardana et al, 2015 ; Ramamoorthy et al, 2022 ). Initially, the individual stress response index (ISRI) for low temperature was calculated as the value of a parameter (P l ) for a given genotype at the low temperature divided by the value of the same parameter at the optimum temperature (P o ; Equation 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports have demonstrated that NUE is controlled genetically, and this complex trait allows optimizing the use of N available to the plant. NUE is equally important when plants experience nutrients shortage or unavailability caused by environmental stresses, such as drought [ 153 , 217 , 218 ], salinity [ 219 ], heat stress [ 220 ], or heavy-metal toxicity, whereby the acquisition of N is either restricted or impaired. In addition to the well-characterized NO 3 or NH 4 transport- and assimilation-related genes [ 221 ], N remobilization (one of the components of NUE) from NO 3 stored in the vacuole regulated through a process known as autophagy carries the potential to salvage poor N supply or transport within the plant, and it offers an alternative for balanced plant productivity and reduced GHG emissions [ 220 , 222 , 223 , 224 ].…”
Section: Paradigm Shift To a Sustainable Agricultural Production Systemmentioning
confidence: 99%